Chinatown (Mayéutica Revista Científica de Humanidades y Artes, 2022)
I give you a rhapsodic text, deliberately scholastic, which proposes itself only Reduce complexity to its informative level. A text that is simple organization of topics, generalities and… minimum guide to Chinese antiquities. These are just Notes.
Keywords: Chinatown; annapocasland